Narratology : Indian perspectives - Rajendran C(ed.); University of Calicut (Delhi : New Bharathiya Book Corp, 2010)
Contributed articles presented at the International Seminar on Narratology on 22-23 February, 2005 at Department of Sanskrit, Calicut University.
Keywords: Literature; Indic literature -- Congresses; Narration (Rhetoric) -- Congresses